Presence of Antibodies to SARS-CoV-2 in Domestic Cats in Istanbul, Turkey, Before and After COVID-19 Pandemic - Yilmaz, Aysun; Kayar, Abdullah; Turan, Nuri; Iskefli, Onur; Bayrakal, Alper; Roman-Sosa, Gleyder; Or, Erman; Tali, Hasan Emre; Kocazeybek, Bekir; Karaali, Ridvan; Bold, Dashzeveg; Sadeyen, Jean-Remy; et al. (Frontiers in Veterinary Science, 2021)
Recent studies demonstrated that domestic cats can be naturally and experimentally infected with severe acute respiratory syndrome coronavirus-2 (SARS CoV-2). This study was performed to investigate the presence of SARS CoV-2-specific antibodies within the domestic cat population in Istanbul, Turkey, before the coronavirus disease 2019 (COVID-19) and during the COVID-19 pandemic. Overall, from 155 cat sera analysed, 26,45% (41/155) tested positive in the spike protein-ELISA (S-ELISA), 28,38% (44/155) in the receptor-binding domain-ELISA (RBD-ELISA) and 21.9% (34/155) in both, the S- and RBD-ELISAs. 27 of those were also positive for the presence of antibodies to feline coronavirus (FCoV). Amongst the 34 SARS CoV-2 positive sera, 3 of those were positive on serum neutralisation assay. Six of the 30 cats before Covid-19 and 28 of the 125 cats during Covid-19 were found to be seropositive. About 20 % of ELISA-positive cats exhibited mainly respiratory, gastrointestinal, and renal signs and skin lesions. Hematocrit, hemoglobin, white blood cells, lymphocyte, and platelet numbers were low in about 30 % of ELISA positive cats. The number of neutrophils and monocytes were above normal values in about 20 % of ELISA-positive cats. The liver enzyme alanine aminotransferase levels were high in 23,5% ELISA-positive cats. In conclusion, this is the first report describing antibodies specific to SARS CoV-2 antigens (S and RBD) in cats in Istanbul, Turkey, indicating the risk for domestic cats to contract SARS-CoV-2 from owners and/or household members with COVID-19. This study and others shows that Covid-19 positive pet owners should limit their contact with companion animals and that pets with respiratory signs should be monitored for SARS-CoV-2 infections.